Penerapan Manajemen Risiko dalam Software Quality Assurance: Studi Kasus Pengujian Black Box pada Aplikasi Inventori Maintenance - Suderajat, Agung; Laki, Abraham Leo Contantinus Meze; Abimanyu, Aldo Anggito; Hadikristanto, Wahyu; Anshor , Abdul Halim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Risk management plays a crucial role in software quality assurance (SQA) to reduce the potential for failures that impact software quality. This study aims to explore the implementation of risk management in black box testing for inventory maintenance applications, focusing on identifying and managing risks that arise within the system. The study employs risk identification, impact analysis, and risk frequency evaluation methods applied to black box testing scenarios. The black box testing results revealed no errors in the system’s features during the tests. This research identifies 18 potential risks, such as feature errors and interface function failures, which can be minimized through mitigation strategies, including user training and preventive and corrective maintenance. The findings conclude that the system design has been well-executed and operates optimally. However, preventive measures are still necessary to ensure the system continues to function effectively.